Freeway Speed Limits under Inclement Weather Conditions - Yonggang Wang; Ming Li; Lei Feng (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
Over the past decade, over speeding has been identified to be the most dominant factor contributing to the occurrence of severe crashes and injuries on freeways, and thus speed limit performs the most popular countermeasure. However, few studies have focused on the problem of freeway speed limits in bad weather due to reduction of visibility and pavement friction. Therefore, the primary purpose of this research is to develop a prototype of speed limits recommendations for basic freeway segments under the inclement weather conditions. If the leading vehicle makes a sudden stop, the travelling distance of the following vehicle is divided into four phases. Assuming the visibility is no less than the safe following distance between consecutive vehicles, consequently, a parabolic equation is constructed to describe the relation between the vehicle’s maximum safe speed, pavement conditions, segment slope and visibility, and then maximum safe speed is rounded down to the nearest multiple of 5 as the proposed speed limit under the fogy, rainy or snowy conditions.